2018
DOI: 10.1002/slct.201702907
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Derived NiO‐Mn2O3/C Nanocomposites as Non‐Precious Catalysts for Enhanced Oxygen Reduction Reaction

Abstract: NiO‐Mn2O3/C nanocomposite was synthesized from chitosan, a renewable biopolymer, NiO and MnO2 and pyrolyzed at 500 °C under nitrogen. The morphology of material was characterized with various microscopic analyses. The graphitic carbon showed metal nanoparticles dispersed on the nanocomposite that could be clearly differentiated. X‐ray photoelectron spectroscopy indicated the Mn species reduced from +4 to +3 oxidation state, while Ni species remained as NiO, which was further supported by X‐ray diffraction. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
(72 reference statements)
1
6
0
Order By: Relevance
“…Transition metal oxides (TMOs) have been widely used in fields of oxygen evolution reaction (OER) [259][260][261], oxygen reduction reaction (ORR) [262][263][264], and photochemical reduction reaction [265][266][267] owing to their environmentally benignity, stability and cost-effective characteristics. Unfortunately, most metal oxides fail to electrocatalyze hydrogen evolution reaction due to their low intrinsic electrical conductivity and inappropriate free energy of hydrogen adsorption [268][269][270][271][272][273].…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…Transition metal oxides (TMOs) have been widely used in fields of oxygen evolution reaction (OER) [259][260][261], oxygen reduction reaction (ORR) [262][263][264], and photochemical reduction reaction [265][266][267] owing to their environmentally benignity, stability and cost-effective characteristics. Unfortunately, most metal oxides fail to electrocatalyze hydrogen evolution reaction due to their low intrinsic electrical conductivity and inappropriate free energy of hydrogen adsorption [268][269][270][271][272][273].…”
Section: Transition Metal Oxidesmentioning
confidence: 99%
“…The average n value (∼3.3) calculated from the RRDE analysis revealed that the Ni-BTB-BPE/C favors the four-electron pathway in 0.1 M KOH. The ORR onset potential and n value of several non-porous Ni-based catalysts are listed in Table S3. For molecular catalysts such as metal macrocycles, MOFs, or MOCs or CP, four-, and two-electron TOF values of ORR specify a quantitative description for selectivity of the ORR catalytic pathway. Using the Ni-BTB-BPE loading (19.6 μg) on RRDE and its molecular weight and formulae (1066.02 g/mole, obtained from single crystal data) information, the Ni sites were calculated to be 44.28 × 10 15 (375 nM cm –2 ).…”
Section: Resultsmentioning
confidence: 99%
“…By performing the peak fitting analysis, it is determined that Ni 2p3/2 exhibits two characteristic peaks . The peak at 854.7 eV is attributed to the Ni 2+ species on the surface of NiO, 856.4 eV is attributed to Ni 3+ species induced by the Ni−O octahedral N 2+ vacancy, and the satellite peak was observed at 862.2 eV . These results explain the presence of NiO in this catalyst; NiO is considered to be the active site for acetylene carbonylation, and its load is critical (Table ).…”
Section: Resultsmentioning
confidence: 99%